Polska kultura i nauka w 1968 roku. Uwarunkowania i podstawowe problemy egzystencji - Król, Eugeniusz Cezary (Rocznik Polsko-Niemiecki, 2010)
The author presents the determinants and basic problems of existence of Polish science and culture in the period preceding the turbulent year of 1968, as well as the events directly related to this key date in Poland’s history. The departure, by Mr Gomułka’s team, from the ‘achievements’ of the Polish October of ’56, that is, from certain concessions of a democratic nature, evoked deep disappointment in both institutions and the scientific, cultural and artistic milieus, and this, in time, led to attempts at protest. The PRP authorities and, most of all, the sections therein which were responsible for science, education and culture, systematically intervened in activities of the respective professional groups. The tightening of censorship, restrictions in the allocation of printing paper for books and periodicals, the closing down of newspapers, weeklies and magazines ‘inconvenient’ from the point of view of the authorities, the lack of opportunities for dialogue and constructive criticism, repressions against those who openly expressed their independent opinions, and the systematic surveillance of the scientific and creative milieus, were only a part of operations undertaken by the PRP powers-that-be in the second half of the 1960s. It was in that climate that a conflict between the state and the Roman Catholic Church was played out in the process of the Polish State Millennium celebrations in 1966, which coincided with the escalation of the party’s conflict with the intellectuals and men and women of letters, as well as with intra-party infighting between factions within the PUWP. It was the shortcomings of the centralised, command economy and the growing shortages in the shops which resulted in Poland’s situation becoming unstable and threatening to explode. The role of the fuse was performed by the events of March 1968, which were enacted in the cultural and scientific milieus: the turbulent meetings of Warsaw’s men and women of letters, the removal of Adam Mickiewicz’s Dziady (Forefathers’ Eve) from the National Theatre’s repertoire, the manifestation in protest against the removal which followed the last performance, and finally, the students’ rally in the courtyard of Warsaw University, as well as the strikes on the part of students and the personnel of higher education institutions in Warsaw and other Polish cities as the continuation of that rally. It was after these events, when the party had launched an anti-intelligentsia campaign, supplemented with an anti-Semite witch hunt and smear campaign, unleashed by the ‘partisans’ faction around Mieczysław Moczar and by Mr Władysław Gomułka himself. An ‘ethnic criterion’ was applied to the Polish scientific and cultural milieus, eliminating, in the climate of a media witch hunt, renowned academic teachers, scholars, film-makers, publishers, journalists, men and women of letters of Jewish extraction and, finally, driving them to emigrate from Poland. The Polish Armed Forces’ participation in the aggression against Czechoslovakia in 1968 evoked another wave of protests in Poland. The world of culture and science and its representatives living in the West expressed solidarity with the Czech and Slovak nations. This resulted in new arrests and the further emigration of the intellectual elites. It was the most dogmatic and anti-liberal faction of the party apparatchiks, supported by secret and overtcollaborators with the security structures, who came from different professional groups that were also related to science, culture and education, which became highly vocal and obtained wide access to the mass media. It was in this period that Polish culture and science toughened up and delivered itself of illusions; however, it also suffered losses, the recouping of which would be a painful process and, subsequently, would subsequently take its full toll of years.